2009
DOI: 10.1080/00958970802376265
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and superoxide dismutase activity of [pyrrolidinium][Co(sulfathiazole)3(pyrrolidine)]

Abstract: Synthesis, crystal structure and superoxide dismutase activity of [pyrrolidinium] [Co(sulfathiazole) 3 (pyrrolidine)], Journal of Coordination Chemistry, 62:6, 951-957,The preparation, spectroscopic properties and crystal structure of [pyrrolidinium] [Co(sulfathiazole) 3 (pyrrolidine)] are reported. The X-ray structure reveals tetrahedral geometry around cobalt. Three sulfathiazole ligands (each in a ,N-binding mode) occupy three positions, while the remaining position is occupied by a disordered pyrrolidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[30] The IR bands at 810-854 and 784-799 cm −1 , υ(H 2 O) of coordinated water, are an indication of the binding of the water molecule to the copper ion.…”
Section: Ir Spectramentioning
confidence: 99%
“…[30] The IR bands at 810-854 and 784-799 cm −1 , υ(H 2 O) of coordinated water, are an indication of the binding of the water molecule to the copper ion.…”
Section: Ir Spectramentioning
confidence: 99%
“…Despite the crystalline nature of the products, neither proved suitable for Xray structure determination. However, an inspection of molecular models, along with consideration of the structure found previously by X-ray crystallography, for a similar complex [pyrrolidinium][Co(stz) 3 (pyrro)] 35 containing a N 4 donor set, suggested that [Mn(stz) 2 (pyrro) 2 ] and [Mn(stz) 2 (pipe) 2 ] may have tetrahedral geometry around central atom. The sulfathiazole ligand has several potential donor atoms, but due to steric constraints, it is probably acting as a monoanionic unidentate chelating agent.…”
Section: Structure Of the Complexesmentioning
confidence: 93%
“…These bands can be attributed to n-* and -* transitions within the Schiff base molecule. The electronic spectrum of the corresponding [CuHL 4l (OAc)] complex in DMSO reveals a broad band at 558 nm assignable to 2 B 1g → 2 A 1g transition [50] which is characteristic of distorted square planar environment around the copper(II) ion (Fig. S2, Supplementary le).…”
Section: Electronic Absorption Spectramentioning
confidence: 99%